[O-Isopropyl-N-(4-nitrophenyl)thiocarbamato-κS]-(tri-4-tolylphosphine-κP)gold(I) - Yeo, Chien Ing *; Tiekink, Edward R. T. * (MDPI, 2018)
The synthesis, spectroscopic characterization and X-ray crystal structure of the title compound, (4-tolyl)3PAu[SC(O-i-Pr)=NC6H4NO2-4] (1) are described. Spectroscopy exhibited the expected features confirming the formation of the compound. The molecular structure of 1 confirms the expected linear P–Au–S coordination geometry defined by thiolate-S and phosphane-P atoms. The nearly 7◦ deviation from linearity is ascribed to the close approach of the imine-bound phenyl group, indicative of a semi-localized Au . . . π(arene) interaction. The three-dimensional molecular packing is consolidated by methyl- and tolyl-C–H . . . O(nitro) and tolyl-C–H . . . π(tolyl) interactions.